Diastolic dysfunction measured by tissue Doppler imaging in children with end-stage renal disease: a report of the RICH-Q study. (5th March 2013) - Schoenmaker, Nikki J.; Kuipers, Irene M.; van der Lee, Johanna H.; Tromp, Wilma F.; van Dyck, Maria; Gewillig, Marc; Blom, Nico A.; Groothoff, Jaap W.
Abstract: Introduction: Early detection of cardiovascular disease in children with end-stage renal disease is essential in order to prevent cardiovascular morbidity and mortality in early adulthood. Tissue Doppler imaging has shown to be a promising method to detect and quantify subtle abnormalities in diastolic function. We therefore compared assessment of diastolic function by conventional echocardiography and tissue Doppler imaging. Methods: We performed conventional echocardiography and tissue Doppler imaging in 38 children with end-stage renal disease and 76 healthy controls. We compared outcomes on parameters related to diastolic function (E/a ratio for conventional echocardiography and E/E′ ratio for tissue Doppler imaging) for both groups using multiple linear regression analysis. Diastolic dysfunction was defined as E/a ratio <1 or E/E′ ratio > 95th percentile for age. To assess the intra-observer reproducibility, the coefficient of variation was calculated. Results : Children with end-stage renal disease had on average a lower E/a ratio (p = 0.004) and a higher mitral and septal E/E′ ratio (both p < 0.001) compared with controls. In all, two children with end-stage renal disease (5%) had diastolic dysfunction according to the E/a ratio, 11 according to the mitral E/E′ ratio (29%), and 16 according to the septal E/E′ ratio (42%) compared with none of the controls (p = 0.109, p < 0.001, and p < 0.001, respectively). The coefficients of variation of the mitral (7%) and septal E/E′ ratio (4%) were smaller than the coefficient of variation of the E/a ratio (11%). Conclusions: Tissue Doppler imaging is a more sensitive and reliable method to detect diastolic dysfunction than conventional E/a ratio in children with end-stage renal disease.